Antiaging, antioxidant flavonoids; synthesis, antimicrobial screening as well as 3D QSAR CoMFA models for the prediction of biological activity - Lumbiny, Bilkis Jahan; Hui, Zhang; Islam, M Azizul (Journal of the Asiatic Society of Bangladesh, Science, 2014)
Flavonoids, polyphenolic heteronuclear compounds which are naturally occurring antioxidants are widely used as antiaging substances. Synthesis of new naturally occuring organic compounds with basic skeleton of chalcones, flavones and oxygenated flavones and their antimicrobial activity were reported by this research group for long. Presently comparative molecular field analysis (CoMFA) implemented in Sybyl 7.3 was conducted on a series of substituted flavones. CoMFA is an effective computer implemented 3D QSAR technique deriving a correlation between set of the biologically active molecules and their 3D shape, electrostatic and hydrogen bonding characteristics employing both interactive graphics and statistical techniques. Evaluation of 38 compounds were served to establish the models with grid spacing (2.0 Å). CoMFA produced best predictive model for compound 1C (2 ? Phenyl ? 1,4 ? benzopyrone) and compound 2C (5 ? Fluoro ? 3?? hydroxy flavone ) among all. Model for compound 2C [r2 conv (no-validation) = 0.956, SEE = 0.211, F value = 111.054) is better than that of compound 1C [r2 conv (no-validation) = 0.955, SEE = 0.212, F value = 110.261) but comparing superimposed model 1C being suggested as the best predictive model. 3D contour maps were generated to correlate the biological activities with the chemical structures of the examined compounds and for further design. DOI: http://dx.doi.org/10.3329/jasbs.v39i2.17856 J. Asiat. Soc. Bangladesh, Sci. 39(2): 191-199, December 2013